Botulism: a laboratory investigation on biological and food samples from cases and outbreaks in Brazil (1982-2001) - Dilma Scala GELLI; Miyoko JAKABI; Aldo de SOUZA (Universidade de São Paulo (USP), 2002)
Laboratory investigation of botulism from 1982 to 2001 confirmed the occurrence of eight positive outbreaks/cases of botulism in Brazil. From those, type A botulism was observed in seven of them. Biological material of one case (serum and feces) was positive in the first step of the bioassay, but the amount of sample was not sufficient for typification. One of the outbreaks that occurred in 2001 was negative for botulinum toxin in samples of serum, gastric washing and feces, collected eight days before the onset of the symptoms in the affected person who was clinically diagnosed as presenting the disease. Other two cases presenting compatible clinical diagnoses presented negative results. However, in those cases, the collection of samples was (1) after antiserum administration or (2) later than eight days of the onset of symptoms. Investigation was performed by mouse bioassay, as described in the Compendium of Methods for the Microbiological Examination of Foods (compiled by American Public Health Association - APHA)11, using specific antiserum from Centers for Disease Control (CDC), USA.